The Influence of Competency and Service Quality on Comunity Satisfaction at Ditresnarkoba Polda, South Kalimantan: English - Juli, Wahyu Juli Sumariyanti; Arsinah, Arsinah Aprilliana Ulandari; Tina, Tina Lestari; Hary, Hary Soegiri (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This research delves into the impacts of competency and service quality on community satisfaction at Ditresnarkoba Polda, South Kalimantan, with member performance acting as an intervening variable. The study reveals that competency and service quality significantly influence member performance and community satisfaction. It was found that member performance mediates the relationship between competency, service quality, and community satisfaction. The findings suggest that investing in training and enhancing professional skills can lead to improved service quality and higher levels of community satisfaction. This paper also offers detailed guidelines for formatting and submitting papers for the conference proceedings.